A high cycle stability button type sodium ion battery and a preparation method and application thereof

CN122889959APending Publication Date: 2026-10-09HENAN KELONG NEW ENERGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611002358.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-07
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0005]本发明旨在解决现有技术中钠离子扣式电池隔膜选择单一、循环性能有待提升的技术问题,通过系统对比不同隔膜材料及其组合方式对钠离子电池循环性能的影响,提供了一种高循环稳定性扣式钠离子电池及其制备方法,该方法通过优化隔膜应用方案显著改善钠离子扣式电池的循环稳定性及容量性能,能够用于钠离子电池正极材料烧结工艺的筛选,大电池的材料筛选、工艺验证或性能评价

Benefits of technology

[0023] 1) Significantly Improved Cycle Performance: This invention significantly improves the cycle performance of coin-type sodium-ion batteries by employing a double-layer laminated composite separator composed of a glass fiber separator and a lithium-ion battery PP/PE separator, and by optimizing the relative positions of the two layers. Experiments show that the double-layer laminated composite separator structure, with the glass fiber separator closer to the negative electrode and the lithium-ion battery PP/PE separator closer to the positive electrode, exhibits better cycle stability than single-layer separators and other separator combinations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889959A_ABST
    Figure CN122889959A_ABST
Patent Text Reader

Abstract

The application discloses a high-cycle-stability button-type sodium ion battery and a preparation method and application thereof, which comprises a positive electrode sheet, a negative electrode sheet and a diaphragm assembly arranged between the positive electrode sheet and the negative electrode sheet, the diaphragm assembly is a double-layer laminated composite diaphragm structure, the laminated sequence is that the side close to the negative electrode sheet is a glass fiber diaphragm, and the side close to the positive electrode sheet is a lithium battery PP / PE diaphragm; through selection of the double-layer laminated composite diaphragm structure and optimization of the relative positions of the double-layer diaphragms, the cycle performance of the button-type sodium ion battery can be obviously improved, wherein the glass fiber diaphragm has high porosity and excellent liquid absorption and liquid retention, can effectively absorb and store electrolyte, and provides sufficient sodium ion transmission channels for the electrolyte; the lithium battery PP / PE diaphragm has good mechanical strength and thermal stability, can effectively inhibit sodium dendrite puncture, improves the safety of the button-type sodium ion battery, and the synergistic effect of the two diaphragms ensures the ion transmission efficiency and enhances the mechanical barrier function of the diaphragm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of sodium-ion battery technology, specifically relating to a coin cell sodium-ion battery with high cycle stability, its preparation method, and its application. Background Technology

[0002] Sodium-ion batteries, with their advantages of abundant and widely distributed sodium resources and low cost, have shown great application potential in large-scale energy storage and low-speed electric vehicles. Button cells, as the core testing platform for sodium-ion battery material research and process optimization, directly affect the accuracy of material evaluation and the efficiency of large-scale battery development due to their cycle stability. The separator, as a key component of sodium-ion batteries, undertakes the core functions of separating the positive and negative electrodes, preventing short circuits, and allowing sodium ion migration; its performance directly determines the cycle life, safety, and electrochemical stability of sodium-ion batteries.

[0003] Currently, sodium-ion coin cells mostly use the single-layer separator design of lithium-ion batteries. However, the electrolyte composition, ion migration characteristics, and sodium dendrite growth patterns of sodium-ion batteries differ significantly from those of lithium-ion batteries. This makes it difficult for traditional single-layer separators to meet the high-performance requirements of sodium-ion coin cells. For example, lithium-ion PP / PE separators have poor wettability to sodium-ion electrolytes, easily leading to increased interfacial impedance; glass fiber separators, while having good wettability, lack mechanical strength and are prone to deformation or being punctured by sodium dendrites; and novel single-layer separators such as polyacrylonitrile nanomaterial separators and nanofiber separators suffer from problems such as sudden capacity changes and insufficient stability during cycling. Furthermore, existing technologies lack systematic research on double-layer separators, especially the impact of the stacking order of double-layer separators, which has not been thoroughly explored, hindering the optimal improvement of sodium-ion battery cycle performance. Therefore, developing a double-layer separator combination that is suitable for sodium-ion systems and exhibits excellent cycle stability, along with a corresponding sodium-ion battery fabrication method, has become an urgent technical problem to be solved in the research and development of large sodium-ion batteries.

[0004] Existing patent document CN201710006354.0 discloses a novel composite lithium-ion battery separator. The process involves soaking and filtering ultrafine glass fibers in a solution containing a crosslinking agent, followed by drying. The treated ultrafine glass fibers are then added to a molten polyethylene or polypropylene mixture with paraffin wax, vigorously stirred to disperse, and then stretched unidirectionally or bidirectionally through an extruder to obtain a composite film. This composite separator retains the excellent insulation, chemical stability, and high porosity of materials such as PP and PE, while effectively improving the supporting strength of PP and PE battery separators and significantly enhancing thermal shrinkage performance. Compared to separators prepared without glass fibers, the prepared composite separator exhibits significantly improved thermal stability while maintaining charge / discharge capacity. However, the technical solution in this patent document is a single-layer composite film system formed by modifying ultrafine glass fibers with polyethylene or polypropylene. It does not involve any related descriptions of double-layer laminated separator systems, nor does it provide any technical inspiration for optimizing the stacking sequence of double-layer separators to improve the electrochemical performance of sodium-ion batteries. Patent document CN202410443984.4 discloses a functionalized separator based on porous materials and its preparation method. The functionalized separator includes a base membrane and a porous material layer coated on the surface of the base membrane. The functionality of the functionalized separator is manifested in the water adsorption, ion conduction and rectification properties of the porous material. The base membrane is selected from one or more composite membranes selected from PE, PP, PET, PI, PDMS, PA, non-woven fabric, and glass fiber membrane. The functionalized separator can effectively capture water in the electrolyte, prevent harmful side reactions, and inhibit the aging of the electrolyte and positive electrode material. The functionalized separator can promote ion transport, uniform ion distribution, and inhibit dendrite formation. Through the above synergistic effects, the functionalized separator can significantly improve the electrochemical performance and cycle life of the battery. Patent document CN202311012373.6 discloses an embedded composite separator, which includes a porous polymer base membrane and a porous material composited within the pores of the base membrane. The porous polymer base membrane is one or a combination of multiple of the following: PE membrane, PP membrane, PP / PE / PP composite membrane, PDMS membrane, PET membrane, PA membrane, PI membrane, glass fiber membrane, and nonwoven fabric. The embedded composite separator can improve the thermal stability and mechanical strength of the separator, enhance battery safety, and the porous material of the embedded composite separator has a rich pore structure, which can improve the liquid absorption and retention rate of the separator, increase the ion transport number and transport rate, inhibit dendrite growth, and improve the rate capability and cycle life of the battery.Patent document CN202110731040.3 discloses a composite-coated sodium-ion battery separator and its preparation method. The composite-coated sodium-ion battery separator includes a base film, a sodium layer coated on one side of the base film, and an alumina layer coated on the side opposite to the base film and on the sodium layer. The sodium layer is coated between the base film and the alumina layer, which can significantly improve the liquid retention capacity of the separator, thereby accelerating the sodium ion transport speed. The accelerated sodium ion transport speed can improve the cycle performance of sodium-ion batteries and reduce the interfacial resistance, preventing sodium dendrites from piercing the separator, thereby improving the safety performance of sodium-ion batteries. However, the technical solutions in the above four patent documents are all about preparing composite separators by modifying base films with functional materials. The base films involve single-layer composite films or double-layer and multi-layer composite separator systems. However, in the above patent documents, they are only used as one option for the base film. There is no record of solving the technical problems of poor electrolyte wettability and insufficient mechanical strength of single-layer separators in sodium-ion batteries using double-layer laminated separator systems. There is also no technical inspiration for optimizing the stacking order of double-layer separators to optimize the electrochemical performance of sodium-ion batteries. Summary of the Invention

[0005] This invention aims to address the technical problems of limited separator selection and insufficient cycle performance in existing sodium-ion coin cells. By systematically comparing the impact of different separator materials and their combinations on the cycle performance of sodium-ion batteries, this invention provides a high-cycle-stability coin cell sodium-ion battery and its preparation method. This method significantly improves the cycle stability and capacity performance of sodium-ion coin cells by optimizing the separator application scheme. It can be used for screening the sintering process of sodium-ion battery cathode materials, as well as for material screening, process verification, or performance evaluation of large batteries.

[0006] To solve the aforementioned technical problems, this invention adopts the following technical solution: a high-cycle-stability coin cell sodium-ion battery, comprising a positive electrode, a negative electrode, and a separator assembly disposed between the positive and negative electrode. The separator assembly is a double-layer laminated composite separator structure, with the stacking order being a glass fiber separator on the side closer to the negative electrode and a lithium-ion PP / PE separator on the side closer to the positive electrode. By selecting a double-layer laminated composite separator structure and optimizing the relative positions of the two separators, the cycle performance of the coin cell sodium-ion battery can be significantly improved. The glass fiber separator has high porosity and excellent liquid absorption and retention properties, effectively adsorbing and storing the electrolyte and providing sufficient sodium ion transport channels. The lithium-ion PP / PE separator has good mechanical strength and thermal stability, effectively suppressing sodium dendrite penetration and improving the safety of the coin cell sodium-ion battery. The synergistic effect of the two separators ensures both ion transport efficiency and enhances the mechanical barrier function of the separator.

[0007] Furthermore, the active material of the positive electrode is one or more of layered oxides, Prussian blue-based materials, and polyanionic materials, wherein the layered oxide is preferably Na[Cu]1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 O2, Prussian blue materials are preferably iron-based Prussian blue Na2Fe[Fe(CN)6], and polyanionic materials are preferably sodium iron pyrophosphate; the active material of the negative electrode is metallic sodium.

[0008] A method for preparing a coin cell sodium-ion battery with high cycle stability, the specific preparation steps of which are as follows:

[0009] Step S1, Slurry preparation: After vacuum drying of the binder PVDF, the solvent NMP is added to prepare a glue solution. The glue solution, conductive agent SP, positive electrode active material and solvent NMP are added to the reaction vessel and dispersed and mixed evenly. Then, solvent NMP is added several times and dispersed and mixed evenly to prepare the positive electrode slurry.

[0010] Step S2, Electrode Fabrication: The positive electrode slurry is evenly coated onto an aluminum foil substrate and dried in a drying oven to obtain the positive electrode sheet. The areal density of the positive electrode sheet is controlled at 80~100 g / m². 2 The compaction density of the positive electrode sheet is controlled at 3.1~3.3 g / cm³. 3 Cut the positive electrode sheet into round pieces and dry them in a vacuum drying oven for later use.

[0011] Step S3: Cut the glass fiber diaphragm and the lithium battery PP / PE diaphragm into round pieces and dry them in a drying oven for later use.

[0012] Step S4: Assemble a high-cycle-stability coin cell sodium-ion battery in the following order: negative electrode shell → spring sheet → gasket → negative electrode sheet → electrolyte impregnation → glass fiber separator → electrolyte impregnation → lithium battery PP / PE separator → electrolyte impregnation → positive electrode sheet → positive electrode shell → sealing.

[0013] Furthermore, in step S1, the mass ratio of the positive electrode active material, conductive agent SP, and binder PVDF is 88~92:4~6:4~6; and the solid content of the positive electrode slurry is 45%~55%.

[0014] Further, the specific preparation process of the positive electrode slurry in step S1 is as follows: add the adhesive, conductive agent SP, positive electrode active material and solvent NMP to the reaction vessel and disperse them at high speed, wherein the dispersion speed is 2000~2500 r / min and the dispersion time is 3~5 min; then add solvent NMP and disperse them at high speed, wherein the dispersion speed is 2500~3000 r / min and the dispersion time is 3~5 min; add solvent NMP again and disperse them at high speed, wherein the dispersion speed is 3000~3500 r / min and the dispersion time is 3~5 min, and finally the positive electrode slurry is prepared.

[0015] Furthermore, in step S2, the drying temperature of the positive electrode sheet in the drying oven is 80~120℃, and the drying time is 30~60min; the drying temperature of the cut positive electrode sheet in the vacuum drying oven is 80~100℃, the drying time is 8~10h, and the vacuum degree is -0.05~-0.08Mpa.

[0016] Furthermore, in step S3, the diaphragm is dried at a temperature of 60-80°C in a drying oven for 2-4 hours.

[0017] Furthermore, the thickness of the glass fiber diaphragm in step S3 is 675 μm, and the thickness of the lithium battery PP / PE diaphragm is 32 μm.

[0018] Furthermore, the assembly process described in step S4 takes place in an argon glove box, where the H2O and O2 contents are both below 0.1 ppm.

[0019] Furthermore, the electrolyte in step S4 is a mixed electrolyte of EC / DMC / EMC with 1 mol / L NaPF6.

[0020] Furthermore, in step S4, the diameter of the glass fiber separator / lithium battery PP / PE separator is greater than the diameter of the negative electrode sheet, which is greater than the diameter of the positive electrode sheet.

[0021] The application of the coin cell sodium-ion battery described in this invention in the screening of cathode material sintering processes and the screening of cathode materials for large-capacity sodium-ion batteries.

[0022] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0023] 1) Significantly Improved Cycle Performance: This invention significantly improves the cycle performance of coin-type sodium-ion batteries by employing a double-layer laminated composite separator composed of a glass fiber separator and a lithium-ion battery PP / PE separator, and by optimizing the relative positions of the two layers. Experiments show that the double-layer laminated composite separator structure, with the glass fiber separator closer to the negative electrode and the lithium-ion battery PP / PE separator closer to the positive electrode, exhibits better cycle stability than single-layer separators and other separator combinations.

[0024] 2) Synergistic Improvement of Interface Properties: In the double-layer laminated composite membrane structure, the glass fiber membrane has high porosity and excellent liquid absorption and retention properties, effectively adsorbing and storing the electrolyte and providing ample sodium ion transport channels; the lithium-ion battery PP / PE membrane has good mechanical strength and thermal stability, effectively suppressing sodium dendrite penetration and improving the safety of sodium-ion batteries. The synergistic effect of the double-layer membrane ensures both ion transport efficiency and enhances the mechanical barrier function of the membrane.

[0025] 3) Process standardization: It provides a clear and repeatable sodium-ion battery preparation process and cycle testing method, which can be directly used for early material screening and process parameter optimization of large sodium batteries, thereby improving R&D efficiency.

[0026] 4) Simple preparation process: This invention does not require complex modification of the separator. The performance of sodium-ion batteries can be effectively improved simply by optimizing the stacking combination of two commercial separators. It is low in cost, highly operable, and suitable for large-scale promotion and application. Attached Figure Description

[0027] Figure 1 The graph shows the cycling performance of the coin sodium-ion batteries prepared in Examples 1-2 and Comparative Examples 1-4 at a 1C rate. Detailed Implementation

[0028] The preparation and testing methods of the present invention are further illustrated below through specific embodiments:

[0029] The button cell battery models described in this invention are CR2016, CR2025, and CR2032, with CR2032 being preferred.

[0030] The button cell described in this invention comprises a negative electrode shell, a spring sheet, a gasket, a negative electrode sheet, a separator, a positive electrode sheet, a positive electrode shell, and an electrolyte. The negative electrode sheet is a composite negative electrode sheet of current collector aluminum foil and metallic sodium, and the positive electrode is a composite positive electrode sheet of current collector aluminum foil and positive electrode active material.

[0031] The thickness of the current collector aluminum foil is 12~20μm, preferably 20μm;

[0032] The separator is one or two of the following: lithium battery PP / PE separator, glass fiber separator, polyacrylonitrile nanomaterial separator, and nanofiber separator. The thickness of the separator is 32~675μm and the number of separator layers is 1~2.

[0033] When the number of layers in the separator is 1, the separator is a lithium battery PP / PE separator, a glass fiber separator, a polyacrylonitrile nanomaterial separator, or a nanofiber separator.

[0034] When the number of layers in the separator is 2, the separator is composed of a glass fiber separator and a lithium battery PP / PE separator. The separator can be used in the following two ways: the glass fiber separator is attached to the negative electrode side and the lithium battery PP / PE separator is attached to the positive electrode side; or the lithium battery PP / PE separator is attached to the negative electrode side and the glass fiber separator is attached to the positive electrode side. Preferred is that the glass fiber separator is attached to the negative electrode side and the lithium battery PP / PE separator is attached to the positive electrode side.

[0035] The electrolyte is a mixture of 1 mol / L NaPF6, EC / DMC / EMC.

[0036] A fabrication process and cycle testing method for a coin cell sodium-ion battery, specifically including the following steps:

[0037] Step S1, Slurry preparation: Vacuum-dry the binder PVDF, add solvent NMP to prepare a 10wt% adhesive solution, weigh a certain amount of adhesive solution into a weighing cup, then add conductive agent SP, positive electrode active material and solvent NMP and disperse at high speed for 3-5 min at a dispersion speed of 2000-2500 r / min, then add solvent NMP and disperse at high speed for 3-5 min at a dispersion speed of 2500-3000 r / min, then add solvent NMP again and disperse at high speed for 3-5 min at a dispersion speed of 3000-3500 r / min, finally preparing the positive electrode slurry.

[0038] Step S2, Electrode Fabrication: The positive electrode slurry obtained in Step S1 is evenly coated onto an aluminum foil substrate to form an electrode. The electrode is then dried in a drying oven. The areal density of the positive electrode is calculated and controlled to be between 80 and 100 g / m³. 2 Adjust the parameters of the roller mill to control the compaction density of the positive electrode sheet between 3.1 and 3.3 g / cm³. 3 The positive electrode sheet is cut into round pieces with a diameter of 12-14 mm, numbered, weighed, and dried in a vacuum drying oven for later use. Commercially available sodium negative electrode sheets with a diameter of 15-16 mm are used directly.

[0039] Step S3, membrane fabrication: Cut the lithium battery PP / PE membrane, glass fiber membrane, polyacrylonitrile nanomaterial membrane, and nanofiber membrane into membrane discs with a diameter of 17~18mm, and bake them in a drying oven.

[0040] Step S4, Battery Assembly: Transfer the prepared positive electrode and separator to a glove box. The assembly sequence for a single-layer separator is: negative electrode shell → spring plate → gasket → negative electrode sheet → electrolyte impregnation → separator → electrolyte impregnation → positive electrode sheet → positive electrode shell → sealing, resulting in a coin cell sodium-ion battery. The assembly sequence for a two-layer separator is: negative electrode shell → spring plate → gasket → negative electrode sheet → electrolyte impregnation → separator → electrolyte impregnation → separator → electrolyte impregnation → positive electrode sheet → positive electrode shell → sealing, resulting in a coin cell sodium-ion battery.

[0041] Step S5, Testing: The assembled button sodium-ion battery is placed in a constant temperature chamber at 25±3℃ for specific capacity testing. After the specific capacity test, the button sodium-ion battery is placed in a constant temperature chamber at 25±3℃ for cycle testing.

[0042] In step S1, the mass ratio of positive electrode active material SP to PVDF is 88~92:4~6:4~6, and the solid content of the positive electrode slurry is 45%-55%.

[0043] In step S2, the positive electrode sheet is dried in a drying oven at a temperature of 80~120℃ for 30~60 min. After the positive electrode sheet is cut into round pieces, it is dried in a vacuum drying oven at a temperature of 80~100℃ for 8~10 h, with a vacuum degree of -0.05~-0.08 MPa.

[0044] In step S3, the diaphragm is dried at a temperature of 60~80℃ in a drying oven for 2~4 hours.

[0045] In step S3, the thicknesses of the lithium-ion battery PP / PE separator, glass fiber separator, polyacrylonitrile nanomaterial separator, and nanofiber separator are 32 μm, 675 μm, 150 μm, and 115 μm, respectively.

[0046] In step S3, four types of separators are used: lithium-ion battery PP / PE separator, glass fiber separator, polyacrylonitrile nanomaterial separator, and nanofiber separator. One or two types of separators are used, and lithium-ion battery PP / PE separator and glass fiber separator are used in combination. The separators are used in the following two ways: the glass fiber separator is attached to the negative electrode side and the lithium-ion battery PP / PE separator is attached to the positive electrode side; or the lithium-ion battery PP / PE separator is attached to the negative electrode side and the glass fiber separator is attached to the positive electrode side.

[0047] In step S4, the assembly environment is an argon glove box, where the H2O and O2 contents are both below 0.1 ppm; the electrolyte amount is 0.1~0.2 g, and the electrolyte is a 1 mol / L NaPF6 EC / DMC / EMC mixed electrolyte.

[0048] In step 5, the specific capacity test steps are as follows: rest for 8-10 hours → charge at a constant current of 0.2C to a voltage of 4.0V → charge at a constant voltage to a cutoff current of 0.05C → rest for 5 minutes → discharge at a constant current of 0.2C to a voltage of 2.0V. The cyclic test steps are as follows: charge at a constant current of 1C to a voltage of 4.0V → charge at a constant voltage to a cutoff current of 0.05C → rest for 5 minutes → discharge at a constant current of 1C to 2.0V → rest for 5 minutes → cycle 100 times or the retention rate is less than 80%.

[0049] The technical solution provided by the present invention will be described in detail below with reference to embodiments and comparative examples:

[0050] Example 1

[0051] Preparation of adhesive solution: 10wt% PVDF adhesive solution is prepared by mixing PVDF and NMP at a mass ratio of 1:9. Weigh 50g of PVDF adhesive, vacuum dry for 4 hours, add 450g of NMP solvent, and mix thoroughly to obtain the adhesive solution.

[0052] Preparation of positive electrode slurry: Weigh out the layered oxide Na[Cu] of the positive electrode active material into a weighing cup. 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 9.2g of O2, 0.4g of conductive agent Super-P, 4g of PVDF adhesive and 4g of solvent NMP were dispersed at high speed for 3 minutes at a dispersion speed of 2500r / min. Then 1g of solvent NMP was added and dispersed at high speed for 3 minutes at a dispersion speed of 3000r / min. Then 1g of solvent NMP was added again and dispersed at high speed for 3 minutes at a dispersion speed of 3500r / min. Finally, the positive electrode slurry was prepared.

[0053] Positive electrode sheet fabrication: The positive electrode slurry is evenly coated onto a 20μm thick aluminum foil substrate, dried in a drying oven to form the electrode sheet. The weight and dimensions of the positive electrode sheet are weighed, and the areal density of the positive electrode sheet is calculated to be 90 g / m³. 2 Adjust the parameters of the roller mill and measure the thickness of the positive electrode sheet to achieve a compaction density of 3.2 g / cm³. 3 The positive electrode sheet was cut into round pieces with a diameter of 14 mm, the round pieces were numbered and weighed, and then placed in a vacuum drying oven to dry for 8 hours. The oven temperature was 100℃ and the vacuum degree was -0.08Mpa.

[0054] Separator fabrication: Cut the lithium battery PP / PE separator and glass fiber separator into 17mm diameter discs, place them in a drying oven and dry for 3 hours at 80℃.

[0055] Battery assembly: Transfer the prepared positive electrode and separator to the glove box, and assemble them in the following order: negative electrode shell → spring plate → gasket → negative electrode sheet → 1 drop of electrolyte → lithium battery PP / PE separator → 1 drop of electrolyte → glass fiber separator → 8 drops of electrolyte → positive electrode sheet → positive electrode shell → seal to obtain a button sodium-ion battery. Wipe the battery clean with lint-free paper dipped in DMC.

[0056] Battery Testing: Place the coin cell sodium-ion batteries in a constant temperature chamber at 23℃ and initiate the specific capacity test step: rest for 10 hours → charge at 0.2C constant current to 4.0V → charge at constant voltage to the cutoff current of 0.05C → rest for 5 minutes → discharge at 0.2C constant current to 2.0V. After the capacity test, place the coin cell sodium-ion batteries in a constant temperature chamber at 23℃ and initiate the cycle test step: charge at 1C constant current to 4.0V → charge at constant voltage to the cutoff current of 0.05C → rest for 5 minutes → discharge at 1C constant current to 2.0V → rest for 5 minutes → cycle 100 times or retain less than 80%.

[0057] Example 2

[0058] Preparation of adhesive solution: 10wt% PVDF adhesive solution is prepared by mixing PVDF and NMP at a mass ratio of 1:9. Weigh 50g of PVDF adhesive, vacuum dry for 4 hours, add 450g of NMP solvent, and mix thoroughly to obtain the adhesive solution.

[0059] Preparation of positive electrode slurry: Weigh out the layered oxide Na[Cu] of the positive electrode active material into a weighing cup. 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 9.2g of O2, 0.4g of conductive agent Super-P, 4g of PVDF adhesive and 4g of solvent NMP were dispersed at high speed for 3 minutes at a dispersion speed of 2500r / min. Then 1g of solvent NMP was added and dispersed at high speed for 3 minutes at a dispersion speed of 3000r / min. Then 1g of solvent NMP was added again and dispersed at high speed for 3 minutes at a dispersion speed of 3500r / min. Finally, the positive electrode slurry was prepared.

[0060] Positive electrode sheet fabrication: The positive electrode slurry is evenly coated onto a 20μm thick aluminum foil substrate, dried in a drying oven to form the electrode sheet. The weight and dimensions of the positive electrode sheet are weighed, and the areal density of the positive electrode sheet is calculated to be 90 g / m³. 2 Adjust the parameters of the roller mill and measure the thickness of the positive electrode sheet to achieve a compaction density of 3.2 g / cm³. 3 The positive electrode sheet was cut into round pieces with a diameter of 14 mm, the round pieces were numbered and weighed, and then placed in a vacuum drying oven to dry for 8 hours. The oven temperature was 100℃ and the vacuum degree was -0.08Mpa.

[0061] Separator fabrication: Cut the lithium battery PP / PE separator and glass fiber separator into 17mm diameter discs, place them in a drying oven and dry for 3 hours at 80℃.

[0062] Battery assembly: Transfer the prepared positive electrode and separator to the glove box, and assemble them in the following order: negative electrode shell → spring plate → gasket → negative electrode sheet → 1 drop of electrolyte → glass fiber separator → 8 drops of electrolyte → lithium battery PP / PE separator → 1 drop of electrolyte → positive electrode sheet → positive electrode shell → seal to obtain a button sodium-ion battery. Wipe the battery clean with lint-free paper dipped in DMC.

[0063] Battery Testing: Place the coin cell sodium-ion batteries in a constant temperature chamber at 23℃ and initiate the specific capacity test step: rest for 10 hours → charge at 0.2C constant current to 4.0V → charge at constant voltage to the cutoff current of 0.05C → rest for 5 minutes → discharge at 0.2C constant current to 2.0V. After the capacity test, place the coin cell sodium-ion batteries in a constant temperature chamber at 23℃ and initiate the cycle test step: charge at 1C constant current to 4.0V → charge at constant voltage to the cutoff current of 0.05C → rest for 5 minutes → discharge at 1C constant current to 2.0V → rest for 5 minutes → cycle 100 times or retain less than 80%.

[0064] Comparative Example 1

[0065] Preparation of adhesive solution: 10wt% PVDF adhesive solution is prepared by mixing PVDF and NMP at a mass ratio of 1:9. Weigh 50g of PVDF adhesive, vacuum dry for 4 hours, add 450g of NMP solvent, and mix thoroughly to obtain the adhesive solution.

[0066] Preparation of positive electrode slurry: Weigh out the layered oxide Na[Cu] of the positive electrode active material into a weighing cup. 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 9.2g of O2, 0.4g of conductive agent Super-P, 4g of PVDF adhesive and 4g of solvent NMP were dispersed at high speed for 3 minutes at a dispersion speed of 2500r / min. Then 1g of solvent NMP was added and dispersed at high speed for 3 minutes at a dispersion speed of 3000r / min. Then 1g of solvent NMP was added again and dispersed at high speed for 3 minutes at a dispersion speed of 3500r / min. Finally, the positive electrode slurry was prepared.

[0067] Positive electrode sheet fabrication: The positive electrode slurry is evenly coated onto a 20μm thick aluminum foil substrate, dried in a drying oven to form the electrode sheet. The weight and dimensions of the positive electrode sheet are weighed, and the areal density of the positive electrode sheet is calculated to be 90 g / m³. 2 Adjust the parameters of the roller mill and measure the thickness of the positive electrode sheet to achieve a compaction density of 3.2 g / cm³. 3 The positive electrode sheet was cut into round pieces with a diameter of 14 mm, the round pieces were numbered and weighed, and then placed in a vacuum drying oven to dry for 8 hours. The oven temperature was 100℃ and the vacuum degree was -0.08Mpa.

[0068] Separator fabrication: Cut the lithium battery PP / PE separator into 17mm diameter discs and dry them in a drying oven at 80℃ for 3 hours.

[0069] Battery assembly: Transfer the prepared positive electrode sheet and lithium battery PP / PE separator to the glove box, and assemble them in the following order: negative electrode shell → spring sheet → gasket → negative electrode sheet → 1 drop of electrolyte → lithium battery PP / PE separator → 9 drops of electrolyte → positive electrode sheet → positive electrode shell → seal to obtain a button sodium-ion battery. Wipe the battery clean with lint-free paper dipped in DMC.

[0070] Battery Testing: Place the coin cell sodium-ion batteries in a constant temperature chamber at 23℃ and initiate the specific capacity test step: rest for 10 hours → charge at 0.2C constant current to 4.0V → charge at constant voltage to the cutoff current of 0.05C → rest for 5 minutes → discharge at 0.2C constant current to 2.0V. After the capacity test, place the coin cell sodium-ion batteries in a constant temperature chamber at 23℃ and initiate the cycle test step: charge at 1C constant current to 4.0V → charge at constant voltage to the cutoff current of 0.05C → rest for 5 minutes → discharge at 1C constant current to 2.0V → rest for 5 minutes → cycle 100 times or retain less than 80%.

[0071] Comparative Example 2

[0072] Preparation of adhesive solution: 10wt% PVDF adhesive solution is prepared by mixing PVDF and NMP at a mass ratio of 1:9. Weigh 50g of PVDF adhesive, vacuum dry for 4 hours, add 450g of NMP solvent, and mix thoroughly to obtain the adhesive solution.

[0073] Preparation of positive electrode slurry: Weigh out the layered oxide Na[Cu] of the positive electrode active material into a weighing cup. 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 9.2g of O2, 0.4g of conductive agent Super-P, 4g of PVDF adhesive and 4g of solvent NMP were dispersed at high speed for 3 minutes at a dispersion speed of 2500r / min. Then 1g of solvent NMP was added and dispersed at high speed for 3 minutes at a dispersion speed of 3000r / min. Then 1g of solvent NMP was added again and dispersed at high speed for 3 minutes at a dispersion speed of 3500r / min. Finally, the positive electrode slurry was prepared.

[0074] Positive electrode sheet fabrication: The positive electrode slurry is evenly coated onto a 20μm thick aluminum foil substrate, dried in a drying oven to form the electrode sheet. The weight and dimensions of the positive electrode sheet are weighed, and the areal density of the positive electrode sheet is calculated to be 90 g / m³. 2 Adjust the parameters of the roller mill and measure the thickness of the positive electrode sheet to achieve a compaction density of 3.2 g / cm³. 3 The positive electrode sheet was cut into round pieces with a diameter of 14 mm, the round pieces were numbered and weighed, and then placed in a vacuum drying oven to dry for 8 hours. The oven temperature was 100℃ and the vacuum degree was -0.08Mpa.

[0075] Separator fabrication: Cut the glass fiber diaphragm into diaphragm discs with a diameter of 17mm, place them in a drying oven and dry for 3 hours at a temperature of 80℃.

[0076] Battery assembly: Transfer the prepared positive electrode and glass fiber separator to the glove box, and assemble them in the following order: negative electrode shell → spring plate → gasket → negative electrode shell → 1 drop of electrolyte → glass fiber separator → 9 drops of electrolyte → positive electrode shell → positive electrode shell → seal to obtain a button sodium-ion battery. Wipe the battery clean with lint-free paper dipped in DMC.

[0077] Battery Testing: Place the coin cell sodium-ion batteries in a constant temperature chamber at 23℃ and initiate the specific capacity test step: rest for 10 hours → charge at 0.2C constant current to 4.0V → charge at constant voltage to the cutoff current of 0.05C → rest for 5 minutes → discharge at 0.2C constant current to 2.0V. After the capacity test, place the coin cell sodium-ion batteries in a constant temperature chamber at 23℃ and initiate the cycle test step: charge at 1C constant current to 4.0V → charge at constant voltage to the cutoff current of 0.05C → rest for 5 minutes → discharge at 1C constant current to 2.0V → rest for 5 minutes → cycle 100 times or retain less than 80%.

[0078] Comparative Example 3

[0079] Preparation of adhesive solution: 10wt% PVDF adhesive solution is prepared by mixing PVDF and NMP at a mass ratio of 1:9. Weigh 50g of PVDF adhesive, vacuum dry for 4 hours, add 450g of NMP solvent, and mix thoroughly to obtain the adhesive solution.

[0080] Preparation of positive electrode slurry: Weigh out the layered oxide Na[Cu] of the positive electrode active material into a weighing cup. 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 9.2g of O2, 0.4g of conductive agent Super-P, 4g of PVDF adhesive and 4g of solvent NMP were dispersed at high speed for 3 minutes at a dispersion speed of 2500r / min. Then 1g of solvent NMP was added and dispersed at high speed for 3 minutes at a dispersion speed of 3000r / min. Then 1g of solvent NMP was added again and dispersed at high speed for 3 minutes at a dispersion speed of 3500r / min. Finally, the positive electrode slurry was prepared.

[0081] Positive electrode sheet fabrication: The positive electrode slurry is evenly coated onto a 20μm thick aluminum foil substrate, dried in a drying oven to form the electrode sheet. The weight and dimensions of the positive electrode sheet are weighed, and the areal density of the positive electrode sheet is calculated to be 90 g / m³. 2 Adjust the parameters of the roller mill and measure the thickness of the positive electrode sheet to achieve a compaction density of 3.2 g / cm³. 3The positive electrode sheet was cut into round pieces with a diameter of 14 mm, the round pieces were numbered and weighed, and then placed in a vacuum drying oven to dry for 8 hours. The oven temperature was 100℃ and the vacuum degree was -0.08Mpa.

[0082] Separator fabrication: The polyacrylonitrile nanomaterial separator is cut into 17mm diameter discs and dried in a drying oven at 80℃ for 3 hours.

[0083] Battery assembly: Transfer the prepared positive electrode and polyacrylonitrile nanomaterial separator to the glove box, and assemble them in the following order: negative electrode shell → spring plate → gasket → negative electrode shell → 1 drop of electrolyte → polyacrylonitrile nanomaterial separator → 9 drops of electrolyte → positive electrode shell → positive electrode shell → seal to obtain a button sodium-ion battery. Wipe the battery clean with lint-free paper dipped in DMC.

[0084] Battery Testing: Place the coin cell sodium-ion batteries in a constant temperature chamber at 23℃ and initiate the specific capacity test step: rest for 10 hours → charge at 0.2C constant current to 4.0V → charge at constant voltage to the cutoff current of 0.05C → rest for 5 minutes → discharge at 0.2C constant current to 2.0V. After the capacity test, place the coin cell sodium-ion batteries in a constant temperature chamber at 23℃ and initiate the cycle test step: charge at 1C constant current to 4.0V → charge at constant voltage to the cutoff current of 0.05C → rest for 5 minutes → discharge at 1C constant current to 2.0V → rest for 5 minutes → cycle 100 times or retain less than 80%.

[0085] Comparative Example 4

[0086] Preparation of adhesive solution: 10wt% PVDF adhesive solution is prepared by mixing PVDF and NMP at a mass ratio of 1:9. Weigh 50g of PVDF adhesive, vacuum dry for 4 hours, add 450g of NMP solvent, and mix thoroughly to obtain the adhesive solution.

[0087] Preparation of positive electrode slurry: Weigh out the layered oxide Na[Cu] of the positive electrode active material into a weighing cup. 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 9.2g of O2, 0.4g of conductive agent Super-P, 4g of PVDF adhesive and 4g of solvent NMP were dispersed at high speed for 3 minutes at a dispersion speed of 2500r / min. Then 1g of solvent NMP was added and dispersed at high speed for 3 minutes at a dispersion speed of 3000r / min. Then 1g of solvent NMP was added again and dispersed at high speed for 3 minutes at a dispersion speed of 3500r / min. Finally, the positive electrode slurry was prepared.

[0088] Positive electrode sheet fabrication: The positive electrode slurry is evenly coated onto a 20μm thick aluminum foil substrate, dried in a drying oven to form the electrode sheet. The weight and dimensions of the positive electrode sheet are weighed, and the areal density of the positive electrode sheet is calculated to be 90 g / m³. 2 Adjust the parameters of the roller mill and measure the thickness of the positive electrode sheet to achieve a compaction density of 3.2 g / cm³. 3 The positive electrode sheet was cut into round pieces with a diameter of 14 mm, the round pieces were numbered and weighed, and then placed in a vacuum drying oven to dry for 8 hours. The oven temperature was 100℃ and the vacuum degree was -0.08Mpa.

[0089] Separator fabrication: Cut the nanofiber separator into 17mm diameter discs and dry them in a drying oven at 80℃ for 3 hours.

[0090] Battery assembly: Transfer the prepared positive electrode and nanofiber separator to the glove box, and assemble them in the following order: negative electrode shell → spring plate → gasket → negative electrode shell → 1 drop of electrolyte → nanofiber separator → 9 drops of electrolyte → positive electrode shell → seal to obtain a button sodium-ion battery. Wipe the battery clean with lint-free paper dipped in DMC.

[0091] Battery Testing: Place the coin cell sodium-ion batteries in a constant temperature chamber at 23℃ and initiate the specific capacity test step: rest for 10 hours → charge at 0.2C constant current to 4.0V → charge at constant voltage to the cutoff current of 0.05C → rest for 5 minutes → discharge at 0.2C constant current to 2.0V. After the capacity test, place the coin cell sodium-ion batteries in a constant temperature chamber at 23℃ and initiate the cycle test step: charge at 1C constant current to 4.0V → charge at constant voltage to the cutoff current of 0.05C → rest for 5 minutes → discharge at 1C constant current to 2.0V → rest for 5 minutes → cycle 100 times or retain less than 80%.

[0092] Experimental results:

[0093]

[0094] In summary, this invention uses different types of separators to fabricate coin-type sodium-ion batteries and studies the influence of the separator on cycle performance.

[0095] As can be seen from the comparison of Examples 1-2 and Comparative Examples 1-4, using a combination of two different types of diaphragms helps to improve cycle performance.

[0096] A comparison between Example 1 and Example 2 shows that the stacking order of the diaphragm affects the cycle performance.

[0097] The results show that the single-layer membrane schemes (Comparative Examples 1-4) all have obvious defects: Comparative Example 1 (lithium-ion battery PP / PE membrane) shows a sudden drop in capacity in the later stage of cycling, Comparative Example 2 (glass fiber membrane) shows violent capacity fluctuations, and Comparative Example 3 (polyacrylonitrile nano membrane) and Comparative Example 4 (nanofiber membrane) both show a sharp capacity decay in the later stage of cycling, which cannot meet the requirements for long-term cycle stability.

[0098] The cycling performance of the double-layer separator scheme (Examples 1-2) is better than that of the single-layer separator, and the stacking order has a significant impact on the performance: Example 2 adopts a double-layer laminated composite separator structure with a glass fiber separator near the negative electrode and a lithium battery PP / PE separator near the positive electrode. It utilizes the excellent electrolyte wettability and electrolyte retention capacity of the glass fiber separator to suppress the disordered growth of sodium dendrites on the negative electrode surface, and the good mechanical strength and thermal stability of the lithium battery PP / PE separator to prevent dendrite penetration. Finally, it achieves a high capacity retention rate of 92.6% for 100 cycles. The cycling process is stable and without sudden changes, which is the optimal separator combination scheme.

[0099] The foregoing has shown and described the basic principles, main features and advantages of the present invention. Various changes and modifications can be made to the present invention without departing from the spirit and scope thereof, and all such changes and modifications fall within the scope of the present invention as claimed.

Claims

1. A high-cycle-stability coin cell sodium-ion battery, comprising a positive electrode, a negative electrode, and a separator assembly disposed between the positive and negative electrode, characterized in that: The separator assembly is a double-layer laminated composite separator structure. Its stacking order is that the side closer to the negative electrode is a glass fiber separator, and the side closer to the positive electrode is a lithium battery PP / PE separator. By selecting a double-layer laminated composite separator structure and optimizing the relative position of the double separators, the cycle performance of the coin cell sodium-ion battery can be significantly improved. The glass fiber separator has high porosity and excellent liquid absorption and retention properties, which can effectively adsorb and store the electrolyte and provide it with sufficient sodium ion transport channels. The lithium-ion battery PP / PE separator has good mechanical strength and thermal stability, which can effectively suppress sodium dendrite puncture and improve the safety of button sodium-ion batteries. The synergistic effect of the two separators not only ensures ion transport efficiency, but also enhances the mechanical barrier function of the separator.

2. The high cycle stability coin cell sodium-ion battery according to claim 1, characterized in that: The active material of the positive electrode is one or more of layered oxides, Prussian blue-based materials, and polyanionic materials, wherein the layered oxide is specifically Na[Cu]. 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 O2, Prussian blue materials specifically iron-based Prussian blue Na2Fe[Fe(CN)6], polyanionic materials specifically sodium iron pyrophosphate; the active material of the negative electrode is metallic sodium.

3. A method for preparing a high-cycle-stability coin cell sodium-ion battery as described in claim 1 or 2, characterized in that... The specific preparation steps are as follows: Step S1, Slurry preparation: After vacuum drying of the binder PVDF, the solvent NMP is added to prepare a glue solution. The glue solution, conductive agent SP, positive electrode active material and solvent NMP are added to the reaction vessel and dispersed and mixed evenly. Then, solvent NMP is added several times and dispersed and mixed evenly to prepare the positive electrode slurry. Step S2, Electrode Fabrication: The positive electrode slurry is evenly coated onto an aluminum foil substrate and dried in a drying oven to obtain the positive electrode sheet. The areal density of the positive electrode sheet is controlled at 80~100 g / m². 2 The compaction density of the positive electrode sheet is controlled at 3.1~3.3 g / cm³. 3 Cut the positive electrode sheet into round pieces and dry them in a vacuum drying oven for later use. Step S3: Cut the glass fiber diaphragm and the lithium battery PP / PE diaphragm into round pieces and dry them in a drying oven for later use. Step S4: Assemble a high-cycle-stability coin cell sodium-ion battery in the following order: negative electrode shell → spring sheet → gasket → negative electrode sheet → electrolyte impregnation → glass fiber separator → electrolyte impregnation → lithium battery PP / PE separator → electrolyte impregnation → positive electrode sheet → positive electrode shell → sealing.

4. The method for preparing a high-cycle-stability coin cell sodium-ion battery according to claim 3, characterized in that: In step S1, the mass ratio of the positive electrode active material, conductive agent SP, and binder PVDF is 88~92:4~6:4~6; the solid content of the positive electrode slurry is 45%~55%.

5. The method for preparing a high-cycle-stability coin cell sodium-ion battery according to claim 3, characterized in that... The specific preparation process of the positive electrode slurry in step S1 is as follows: add the adhesive, conductive agent SP, positive electrode active material and solvent NMP to the reaction vessel and disperse them at high speed, wherein the dispersion speed is 2000~2500 r / min and the dispersion time is 3~5 min. Then add solvent NMP and disperse at high speed, wherein the dispersion speed is 2500~3000 r / min and the dispersion time is 3~5 min. Add solvent NMP again and disperse at high speed, wherein the dispersion speed is 3000~3500 r / min and the dispersion time is 3~5 min, and finally the positive electrode slurry is prepared.

6. The method for preparing a high-cycle-stability coin cell sodium-ion battery according to claim 3, characterized in that: In step S2, the positive electrode sheet is dried at a temperature of 80~120℃ in the drying oven for 30~60 min; the cut positive electrode sheet is dried at a temperature of 80~100℃ in the vacuum drying oven for 8~10 h, with a vacuum degree of -0.05~-0.08 MPa; in step S3, the separator is dried at a temperature of 60~80℃ in the drying oven for 2~4 h.

7. The method for preparing a high-cycle-stability coin cell sodium-ion battery according to claim 3, characterized in that: The thickness of the glass fiber diaphragm in step S3 is 675 μm, and the thickness of the lithium battery PP / PE diaphragm is 32 μm.

8. The method for preparing a high-cycle-stability coin cell sodium-ion battery according to claim 3, characterized in that: The assembly process in step S4 takes place in an argon glove box, where the H2O and O2 contents are both below 0.1 ppm; the electrolyte is a 1 mol / L NaPF6 EC / DMC / EMC mixed electrolyte.

9. The method for preparing a high-cycle-stability coin cell sodium-ion battery according to claim 3, characterized in that: In step S4, the diameter of the glass fiber separator / lithium battery PP / PE separator is greater than the diameter of the negative electrode sheet, which is greater than the diameter of the positive electrode sheet.

10. The application of the button-type sodium-ion battery as described in claim 1 or 2 in the screening of cathode material sintering processes and the screening of cathode materials for large-capacity sodium-ion batteries.

Citation Information

Patent Citations

  • Novel composite diaphragm for lithium ion battery

    CN106711381A

  • A composite coated sodium-ion battery separator and its preparation method

    CN113675533B

  • Embedded composite diaphragm

    CN116885391A

  • Functional diaphragm based on porous material and preparation method thereof

    CN118299764A